## Results (displaying matches 1-50 of 5089) Next

Label Class Equation Sato-Tate $$\overline{\Q}$$-simple $$\GL_2$$ Rank*
249.a.249.1 249.a $$y^2 + (x^3 + 1)y = x^2 + x$$ $\mathrm{USp}(4)$ 0
277.a.277.1 277.a $$y^2 + (x^3 + x^2 + x + 1)y = -x^2 - x$$ $\mathrm{USp}(4)$ 0
295.a.295.1 295.a $$y^2 + (x^3 + 1)y = -x^2$$ $\mathrm{USp}(4)$ 0
349.a.349.1 349.a $$y^2 + (x^3 + x^2 + x + 1)y = -x^3 - x^2$$ $\mathrm{USp}(4)$ 0
363.a.11979.1 363.a $$y^2 + (x^2 + 1)y = x^5 + 2x^3 + 4x^2 + 2x$$ $G_{3,3}$ 0
464.a.29696.1 464.a $$y^2 + (x + 1)y = 8x^5 + 3x^4 - 4x^3 - 2x^2$$ $\mathrm{USp}(4)$ 0
472.a.944.1 472.a $$y^2 + (x^2 + 1)y = x^5 - x^4 - 2x^3 + x$$ $\mathrm{USp}(4)$ 0
555.a.8325.1 555.a $$y^2 + (x + 1)y = 3x^5 - 2x^4 - 4x^3 + x^2 + x$$ $\mathrm{USp}(4)$ 0
704.a.45056.1 704.a $$y^2 + y = 4x^5 + 4x^4 - x^3 - 2x^2$$ $\mathrm{USp}(4)$ 0
741.a.28899.1 741.a $$y^2 + (x + 1)y = -3x^5 - x^4 + 2x^2 + x$$ $\mathrm{USp}(4)$ 0
762.a.82296.1 762.a $$y^2 + (x^2 + x)y = x^5 - 8x^4 + 14x^3 + 2x^2 - x$$ $\mathrm{USp}(4)$ 0
826.a.11564.1 826.a $$y^2 + (x^2 + x)y = x^5 + x^4 + 3x^3 - 4x^2 - 4x + 3$$ $\mathrm{USp}(4)$ 0
830.a.6640.1 830.a $$y^2 + (x^3 + 1)y = -x^5 + x^4 - 2x^2 + x + 1$$ $\mathrm{USp}(4)$ 0
830.a.830000.1 830.a $$y^2 + (x^2 + x)y = x^5 - 2x^4 + 16x^3 + 8x^2 + x$$ $\mathrm{USp}(4)$ 0
856.a.1712.1 856.a $$y^2 + (x^3 + x)y = -x^4 - x^3 + x$$ $\mathrm{USp}(4)$ 0
862.a.6896.1 862.a $$y^2 + (x^2 + x)y = 4x^5 + 6x^4 - 3x^2 - x$$ $\mathrm{USp}(4)$ 0
886.a.3544.1 886.a $$y^2 + (x^3 + x)y = -x^4 - x + 1$$ $\mathrm{USp}(4)$ 0
909.a.8181.1 909.a $$y^2 + xy = 3x^5 - 7x^4 + x^3 + 6x^2 - 3x$$ $\mathrm{USp}(4)$ 0
925.a.23125.1 925.a $$y^2 + xy = 5x^5 + x^4 - 19x^3 + 18x^2 - 5x$$ $\mathrm{USp}(4)$ 0
1012.a.4048.1 1012.a $$y^2 + (x^3 + 1)y = x^4 + x^3 + x^2 + x$$ $\mathrm{USp}(4)$ 0
1164.b.670464.1 1164.b $$y^2 + (x^2 + x + 1)y = 2x^5 - 2x^4 + x^3 - x^2$$ $\mathrm{USp}(4)$ 0
1180.a.18880.1 1180.a $$y^2 + (x^3 + 1)y = -2x^4 + 4x^2 + 2x$$ $\mathrm{USp}(4)$ 0
1184.a.606208.1 1184.a $$y^2 = 2x^5 + x^4 - 8x^3 - 8x^2 - 2x$$ $\mathrm{USp}(4)$ 0
1272.a.122112.1 1272.a $$y^2 + (x^2 + 1)y = 3x^5 + 4x^4 + 2x^3 - x^2 - x$$ $\mathrm{USp}(4)$ 0
1311.a.814131.1 1311.a $$y^2 + xy = x^5 + 5x^4 + 5x^3 + 4x^2 + x$$ $\mathrm{USp}(4)$ 0
1338.b.72252.1 1338.b $$y^2 + (x^2 + x)y = x^5 + 7x^4 + 4x^3 - 12x^2 - 6x + 5$$ $\mathrm{USp}(4)$ 0
1408.b.180224.2 1408.b $$y^2 = 2x^5 - 4x^3 - x^2 + 2x + 1$$ $\mathrm{USp}(4)$ 0
1416.a.8496.1 1416.a $$y^2 + (x^3 + x)y = x^5 - x^3 - 1$$ $\mathrm{USp}(4)$ 0
1468.b.5872.1 1468.b $$y^2 + (x^2 + x + 1)y = -2x^5 - 2x^4$$ $\mathrm{USp}(4)$ 0
1624.a.831488.1 1624.a $$y^2 + (x^3 + x)y = x^5 + 2x^3 + 2x^2 + x + 1$$ $\mathrm{USp}(4)$ 0
1689.a.1689.1 1689.a $$y^2 + (x^2 + x + 1)y = x^5 + 2x^4 + 2x^3 + x^2$$ $\mathrm{USp}(4)$ 1
1702.a.39146.1 1702.a $$y^2 + (x + 1)y = x^5 - 13x^3 + 14x^2 + 22x - 30$$ $\mathrm{USp}(4)$ 1
1717.b.1717.1 1717.b $$y^2 + (x^3 + x)y = -x^4 - 2x^3 - 2x^2 - x$$ $\mathrm{USp}(4)$ 1
1728.a.27648.1 1728.a $$y^2 + (x + 1)y = 3x^6 - 3x^4 - x^3$$ $\mathrm{USp}(4)$ 0
1740.a.104400.1 1740.a $$y^2 + (x^2 + x)y = 2x^5 - 14x^3 - 5x^2 + 30x$$ $\mathrm{USp}(4)$ 0
1813.a.1813.1 1813.a $$y^2 + y = x^5 + x^4 + 2x^3 + x^2 + x$$ $\mathrm{USp}(4)$ 1
1832.b.14656.1 1832.b $$y^2 + (x + 1)y = 2x^5 - 4x^3 - 2x^2$$ $\mathrm{USp}(4)$ 0
1896.a.728064.1 1896.a $$y^2 + (x^3 + x)y = x^5 - 2x^4 - 8x^3 + 11x - 3$$ $\mathrm{USp}(4)$ 0
1929.a.1929.1 1929.a $$y^2 + (x^2 + x + 1)y = x^5 - x^4 + x^3 - x^2$$ $\mathrm{USp}(4)$ 1
1944.a.34992.1 1944.a $$y^2 + xy = 2x^5 + 2x^4 - 3x^2 + x$$ $\mathrm{USp}(4)$ 0
1996.b.510976.1 1996.b $$y^2 + (x^3 + x^2 + x)y = x^3 + x^2 + 3x + 1$$ $\mathrm{USp}(4)$ 0
2121.a.400869.1 2121.a $$y^2 + xy = x^5 - 2x^4 - 4x^3 + 8x^2 - 1$$ $\mathrm{USp}(4)$ 0
2154.a.465264.1 2154.a $$y^2 + (x^2 + x)y = x^5 - 9x^3 - x^2 + 18x - 1$$ $\mathrm{USp}(4)$ 0
2188.a.140032.1 2188.a $$y^2 + (x^2 + x + 1)y = -4x^5 - 4x^4 - x^2 - x$$ $\mathrm{USp}(4)$ 0
2208.b.847872.1 2208.b $$y^2 = 3x^5 - 4x^4 - 3x^3 + x^2 + 4x$$ $\mathrm{USp}(4)$ 0
2214.a.816966.1 2214.a $$y^2 + (x + 1)y = x^5 + 3x^4 - 56x^3 + 27x^2 - 5x$$ $\mathrm{USp}(4)$ 1
2288.a.805376.1 2288.a $$y^2 + (x + 1)y = -4x^5 - x^4 - x^3 - x^2$$ $\mathrm{USp}(4)$ 0
2320.b.185600.1 2320.b $$y^2 + (x^3 + x)y = -x^4 - x^3 - x + 1$$ $\mathrm{USp}(4)$ 0
2335.a.2335.1 2335.a $$y^2 + (x + 1)y = -x^5 - x^4 - x^3$$ $\mathrm{USp}(4)$ 1
2470.a.321100.1 2470.a $$y^2 + xy = 5x^5 + 9x^4 + 13x^3 + 9x^2 + 5x + 1$$ $\mathrm{USp}(4)$ 1
Next